Long Non-Coding RNAs in Lung Cancer: The Role in Tumor Microenvironment - Dai, Shuang; Liu, Ting; Liu, Yan-Yang; He, Yingying; Liu, Tao; Xu, Zihan; Wang, Zhi-Wu; Luo, Feng (Frontiers in Cell and Developmental Biology, 2022)
The development of various therapeutic interventions, particularly immune checkpoint inhibitor therapy, have effectively induced tumor remission for patients with advanced lung cancer. However, few cancer patients can obtain significant and long-lasting therapeutic effects for the limitation of immunological nonresponse and resistance. For this case, it’s urgent to identify new biomarkers and develop therapeutic targets for future immunotherapy. Over the past decades, tumor microenvironment (TME)-related long non-coding RNAs (lncRNAs) have gradually become well known to us. A large number of existing studies have indicated that TME-related lncRNAs are one of the major factors to realize precise diagnosis and treatment of lung cancer. Herein, this paper discusses the roles of lncRNAs in TME, and the potential application of lncRNAs as biomarkers or therapeutic targets for immunotherapy in lung cancer.